What about applied kinanthropometry in wheelchair basketball? Proposal for anthropometric references in Spanish elite players - Buceta-Toro, M. I.; Perpiñá-Martínez, S.; Aprea-Moreno, S.; Delgado Ortiz, S.; Ausó, E.; Cifuentes, A.; Sospedra, I.; Norte, A.; Romero-Garcia, D.; Martínez-Sanz, J. M.; Leardy Palencia, P.; Miana, M. (Sports Medicine - Open, 2025)
Background Disability negatively impacts body composition due to muscle disuse in paralyzed or amputated limbs. This study aimed to describe and compare the anthropometric profile and body composition of professional wheelchair basketball players according to their functional classification. In this cross-sectional descriptive study, a non-probabilistic convenience sampling of professional wheelchair basketball teams competing in the Honor Division was performed. Anthropometric measurements were taken according to ISO 7250-1:2017 and the International Society for the Advancement of Kinanthropometry (ISAK) standard. Body mass, sitting height, arm span, six skinfolds, girth, breadth, and lengths were collected. SPSS version 27 was used for general descriptive analysis and by functional groups, and for inferential analysis and calculation of percentiles tables in men.